Morphologic Characteristic of Coronary Artery Disease, with Emphasis on Thromboses, in Patients Younger Than 40 Years of Age. (28th September 2009) - Tavora, Fabio; Li, Ling; Ripple, Mary; Fowler, David; Burke, Allen
Abstract : There are few pathologic descriptions of fatal coronary artery disease in the young. The morphologic characteristics of sudden coronary deaths in 47 hearts from patients younger than 40 years were studied. Numbers of plaques with necrotic cores were quantitated in each heart. Compared to 194 sudden coronary deaths >40 years, heart weight was lower, acute plaque erosions more frequent, and extent of disease less in the≤ 40 years group. Plaque burden was less in hearts with erosions, and healed infarcts more common in hearts with stable plaque. The numbers of fibroatheromas increased with age until the 6th decade (P < .0001 ) as well as the proportion of total plaques that were atheromatous. Plaques in younger patients have fewer lipid-rich cores. Most thrombi show areas of organization, with layering frequent in erosions, suggesting a possible method of plaque enlargement in the absence of necrotic core formation.